PENDAMPINGAN KELOMPOK BELAJAR PENDIDIKAN H. SAHLAN DALAM MENJAGA BIODIVERSITAS TUMBUHAN OBAT KELUARGA - Ni Ketut Kariani; Wendi Muhammad Fadhli; Maharani Farah Dhifa Dg Masikki; Sinta Pratiwi; Nur Aini; Aulin Kristika; Iin Alizzah Adam Lawi; Nurfadhillah Nurfadhillah; Wulan Antarik Ragi (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Based on the results of the interviews we conducted, there is a problem that occurred in Group H. Sahlan, namely since the earthquake and tsunami in 2018 the medicinal plants in the TOGA garden have become unmaintained and since then no nursery has been carried out again. After the PPK Ormawa HIMADIKSIKIP team developed a medicinal plant conservation area in the H.Sahlan group. So it is necessary to assist conservation areas to maintain the biodiversity of family medicinal plants in H. Sahlan's garden. The purpose of implementing PPK Ormawa HIMADIKSIKIP activities is to help the H.Sahlan group family medicinal plant biodiversity area be maintained. The mentoring method is a method used by the team in community service activities to achieve the target of mentoring the H. Sahlan group. Based on the results of six months of dedication, the results of mentoring the biodiversity-based medicinal plant conservation area of Pakuli village have a successful program, namely mapping the potential of medicinal plant biodiversity. H.Sahlan group has the ability to be a local guide in explaining related to medicinal plants and business management skills of medicinal plant businesses. It was concluded that the mentoring program activities had been successful